Dynamics and associations of selected agrometeorological variables in Robusta growing regions of Uganda - Ronald Ssembajwe; Catherine Mulinde; Saul D. Ddumba; Godfrey H. Kagezi; Ronald Opio; Judith Kobusinge; Frank Mugagga; Yazidi Bamutaze; Anthony Gidudu; Geoffrey Arinaitwe; Mihai Voda (Agricultural Water Management)
As climate variability increases with extremes becoming more frequent, the pressure on agriculture only intensifies. A better understanding of the dynamics of direct climate drivers of agricultural productivity is therefore sought. This study aimed to analyze the long-term and recent spatiotemporal trends and associations of selected agrometeorological variables in Robusta Coffee growing regions (RCGR) of Uganda for the period 1980–2021. We employed novel trend test and signal decomposition methods along with machine learning and correlation methods. Results show significantly increasing trends in monthly Vapor Pressure Deficit (VPD) in Amolatar, Kabale and Mbale while, Arua, Kituza and Masindi had decreasing trends. Additionally, significantly decreasing trends in Fraction of Absorbed Photosynthetically Active Radiation (FAPAR) except for Masindi, Abim and Amolatar districts in Kyoga basin were observed. However, there were generally no trends in Climate Water Balance (CWB) and Actual Evapotranspiration (AET) over the study region at 5 % level of significance. BEAST results revealed significant changes in Mbale’s seasonal AET, abrupt changes in both trends and seasons of Kituza AET since 1982 with 10 % chances of occurrence, trend anomalies in Amolatar VPD since 2009. Furthermore, significantly decreasing and increasing trends in Potential Evapotranspiration (PET) and NPP respectively were observed across 70 % of the RCGR. El-Nino/Southern Oscillations accounted for only 2.5 % of the variance in PET. Strong negative and positive associations were observed between PET and NPP in the Northern sub region and Mid-Eastern stretch respectively. Therefore, urgent interventions in form of seasonal schedule restructuring and optimal irrigation use and management to increase productivity especially in areas where CWB is below 0 for over 3 months, offset the increasing VPD and as well effectively manage pest and diseases are recommended.